The Role of Purinergic Mechanisms in the Excitability of Trigeminal Afferents of Rats with Prenatal Hyperhomocysteinemia - Elizaveta Ermakova; Svetlana Svitko; Alsu Kabirova; Egor Nevsky; Olga Yakovleva; Karina Gilizhdinova; Kseniia Shaidullova; Anton Hermann; Guzel Sitdikova (Biomolecules)
Elevated levels of homocysteine in the blood plasma (hyperhomocysteinemia, HHCY) positively correlate with migraine symptoms in patients. Experimental studies show a higher sensitivity of rats with prenatal HHCY (pHHCY) to migraine symptoms like allodynia, photophobia, anxiety, and a higher excitability of meningeal trigeminal afferents. In the present study, the roles of purinergic mechanisms in the homocysteine-induced hyperexcitability of the trigeminal ganglion (TG) system using electrophysiological recordings from the trigeminal nerve, Ca2+ imaging of cells isolated from TG, and mast cell staining in meninges were investigated. Experiments were performed using rats with pHHCY born from females fed with a high-methionine-containing diet before and during pregnancy. Firstly, we found that lower concentrations of 4-aminopyridine, a K+-channel blocker, were able to induce an increase in the nociceptive activity of trigeminal afferents, supporting the hypothesis of the higher excitability of the trigeminal nerve of rats with pHHCY. Trigeminal afferents of rats with pHHCY were more sensitive to the exogenous application of the nonspecific agonist of purinergic ATP receptors. In neurons and satellite glial cells of TG of rats with pHHCY ATP, ADP (an agonist of metabotropic P2Y receptors) and BzATP (an agonist of ionotropic P2X with especially high potency for the P2X7 receptor) induced larger Ca2+ transients. The incubation of TG neurons in homocysteine for 24 h increased the ratio of neurons responding simultaneously to ATP and capsaicin. Moreover, rats with pHHCY exhibit a higher rate of degranulation of mast cells and increased response to the agonist of the P2X7 receptor BzATP application. In addition, higher levels of calcitonin gene-related peptide (CGRP) were found in rats with pHHCY. Our results suggest that chronic elevated levels of homocysteine induce the upregulation of ionotropic or metabotropic ATP receptors in neurons, satellite glial cells, and mast cells, which further provide inflammatory conditions and the sensitization of peripheral afferents underlying pain.